Changes in African large carnivore diets over the past half‐century reveal the loss of large prey. Issue 6 (5th July 2018) - Creel, Scott; Matandiko, Wigganson; Schuette, Paul; Rosenblatt, Elias; Sanguinetti, Carolyn; Banda, Kambwiri; Vinks, Milan; Becker, Matthew
Abstract: Globally, large carnivores are declining due to direct persecution, habitat loss, and prey depletion. The effects of prey depletion could be amplified by changes in the composition of the herbivore (prey) community that provoke changes in carnivore diets, but this possibility has received little attention. We tested for changes over the past half‐century in prey selection by the large carnivore guild in Zambia's Kafue National Park (KNP). Across 52 predator–prey dyads, 71% of the observed changes showed that large prey have become less important and small prey have become more important. Consequently, dietary niche breadth has decreased for KNP carnivores and niche overlap has increased. We tested whether changes in the importance of prey species are related to their current abundance and uniformly found that prey that have increased in importance are now relatively common, while those that have decreased in importance are now relatively rare. We identify four potential effects of these changes for conservation (through intraguild competition, group size, the energetics of hunting, and vulnerability to snaring) that warrant investigation. Synthesis and applications . Patterns of prey selection by the large carnivores in Kafue National Park (KNP) have changed appreciably over the past half‐century. Decreased predation on large prey, which are now relatively rare, has caused niche compression and increased overlap in carnivore diets. Predation by all KNP large carnivores now concentrates on four small prey species that remain relatively abundant (impala, puku, lechwe, and warthog). Methods to detect such changes in interactions between species are well‐established, but are rarely applied to large carnivore‐ungulate systems. To guide conservation of ecosystem function, monitoring programmes should consider whether prey depletion alters the patterns of predation or competition within the predator guild because these interactions strongly affect the distribution and abundance of both predators and prey. If the patterns seen in KNP are general, then where carnivores are limited by prey depletion, conservation efforts will be most effective if they focus on mitigating the loss of large prey. In KNP, targeted efforts to protect prey larger than 200 kg, particularly buffalo, should be a priority. Abstract : Patterns of prey selection by the large carnivores in Kafue National Park (KNP) have changed appreciably over the past half‐century. Decreased predation on large prey, which are now relatively rare, has caused niche compression and increased overlap in carnivore diets. Predation by all KNP large carnivores now concentrates on four small prey species that remain relatively abundant (impala, puku, lechwe, and warthog). Methods to detect such changes in interactions between species are well‐established, but are rarely applied to large carnivore‐ungulate systems. To guide conservation of ecosystem function, monitoring programmes should consider whether prey depletion alters the patterns of predation or competition within the predator guild because these interactions strongly affect the distribution and abundance of both predators and prey. If the patterns seen in KNP are general, then where carnivores are limited by prey depletion, conservation efforts will be most effective if they focus on mitigating the loss of large prey. In KNP, targeted efforts to protect prey larger than 200 kg, particularly buffalo, should be a priority.